2016
DOI: 10.1007/s11270-016-3082-x
|View full text |Cite
|
Sign up to set email alerts
|

Waterfowl Impoundments as Sources of Nitrogen Pollution

Abstract: Hydrologically controlled moist-soil impoundment wetlands provide critical habitat for high densities of migratory bird populations. Nutrients exported from heavily used impoundments by prescribed seasonal drawdown of surface water may contribute to the eutrophication of aquatic ecosystems. To investigate the relative importance of nutrient export from managed impoundment habitats, we conducted a field study at Mattamuskeet National Wildlife Refuge in North Carolina, USA, which contains 1545 ha of impoundments… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…Winton et al 2016), a range similar to N loading estimates for fertilized agricultural lands in table 1. Hydrologic drawdown and total N export across two years from impoundment MI10N at Mattamuskeet National Wildlife Refuge in North Carolina, USA.…”
supporting
confidence: 75%
See 1 more Smart Citation
“…Winton et al 2016), a range similar to N loading estimates for fertilized agricultural lands in table 1. Hydrologic drawdown and total N export across two years from impoundment MI10N at Mattamuskeet National Wildlife Refuge in North Carolina, USA.…”
supporting
confidence: 75%
“…We found that the long-term N removal process of denitrification was limited at our field site proximally by low nitrate, and ultimately by herbivory and the lack of plant-mediated O 2 transport. Based on depth of water drawdown and surface water N concentrations we estimate that the impoundment exported 14 and 22 kg N/ha to Lake Mattamuskeet in 2013 and 2014, respectively (Table 1, Winton et al 2016), a range similar to N loading estimates for fertilized agricultural lands in the North Carolina coastal plain (Deal et al 1986). Given that eutrophication of ecosystems is a growing concern globally (Smith 2003), as well as locally at Lake Mattamuskeet (North Carolina Department of Health Environment and Natural Resources 2013, U.S.…”
Section: Resultsmentioning
confidence: 99%
“…During the wet year, the flamingo population size was substantially larger than in the dry year, as were their corresponding N and P inputs (16.7 Kg N ha −1 y −1 and 1.24 Kg P ha −1 y −1 ). These values were higher than those reported for herbivorous (1.07 kg N ha −1 y −1 and 0.10 kg P ha −1 y −1 ) or carnivorous (0.26-0.65 kg N ha −1 y −1 and 0.12-0.16 Kg P ha −1 y −1 ) waterbirds in the Netherlands 4 , 5 , or in Lake Mattamuskeet (0.2 kg N ha −1 y −1 ) in North Carolina 67 . On the other hand, these allochthonous inputs of N and P from flamingo guano were higher than the atmospheric inputs of 5.89 Kg N ha −1 y −1 and 0.18 Kg P ha −1 y −1 reported for the study region 68 .…”
Section: Discussionmentioning
confidence: 99%
“…The sources of these nutrients are diverse, but primarily include agricultural run-off, atmospheric deposition, and pumping of waterfowl impoundments. Waterfowl themselves appear to be an insignificant source (Winton et al 2016). In-situ recycling of sediment and nutrients in the lake could also play a major role in the nutrient budget and is being investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these farmlands connect to the lake via a series of drainage ditches, some of which are equipped with pumps that move water rapidly off the landscape and into the lake. In addition, approximately 6,880 ha of farmland and wetlands are managed intensively for waterfowl during the winter, and these lands typically pump their waters into the lake in late winter and early spring each year (Winton et al 2016). Although precipitation is the main hydrologic input, drainage from managed wetlands and agriculture are secondary water inputs into the lake.…”
Section: Study Sitementioning
confidence: 99%